Novel preparation of CMK-3 nanostructured material modified with titania applied in hydrogen uptake and storage. - Juárez , Juliana María; Ledesma , Brenda Cecilia; Gómez Costa, Marcos Bruno; Beltramone, Andrea Raquel; Anunziata , Oscar Alfredo; Anunziata , Oscar Alfredo; Ledesma , Brenda Cecilia (Univesidsad Tecnológica Nacional., 2016)
This work deals with the development of a novel procedure to synthesize titania-modified nano structured carbon employing Ti-SBA-15 as hard template. The new mesoporous carbon displays high specific surface area of 1044 m2/g and large pore volume of 0.7 cm3/g. XRD pattern of Ti-CMK-3 indicates that the ordered structure of this material is similar to the CMK-3. XRD, XPS and UVeVis-DRS analysis indicated that Ti is highly dispersed as anatase phase in Ti-CMK-3. The synthesized Ti-CMK-3 exhibited significantly enhanced H2 storage properties (2.6 wt%, equivalent to 13 mmol/g) compared with CMK-3 without Ti (2.2 wt%, 11 mmol/g) at 77 K and 10 bar.
Keywords: Hard template method Ti-SBA-15; Ti-CMK-3; Porous materials; Energy storage